1988
DOI: 10.2166/wst.1988.0333
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycete Scum Problems in Australian Activated Sludge Plants

Abstract: The formation of extensive, biological foams or scums on the liquid surfaces of domestic activated sludge plants in Australia was investigated. A survey of the problem in Queensland and Australia was carried out; the dominant organisms in the foam were isolated and identified; their physiology was investigated and the intrinsic reasons for foam formation were explored in the laboratory. Foaming in activated sludge plants was found to be a significant problem in Australia. Greater than 90% of plants in Queensla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This was a somewhat unexpected effect, since actinomycetes are known to be problematic microorganisms in biological wastewater treatment, causing viscous foam or scum on the surfaces of activated sludge aeration tanks. [14][15][16] In this study, we analyzed the mechanism of enhancement of denitrification activity and the possible interactions between these two bacteria.…”
mentioning
confidence: 99%
“…This was a somewhat unexpected effect, since actinomycetes are known to be problematic microorganisms in biological wastewater treatment, causing viscous foam or scum on the surfaces of activated sludge aeration tanks. [14][15][16] In this study, we analyzed the mechanism of enhancement of denitrification activity and the possible interactions between these two bacteria.…”
mentioning
confidence: 99%
“…The sludge bulking is a frequently occurring phenomenon in wastewater treatment plants (WWTPs), which mainly associates with the excessive growth of filamentous bacteria (Blackall et al 1988;de los Reyes et al 2002;Lienen et al 2014;Martins et al 2004;Rossetti et al 2005), and results in sludge separation problems like Bbulking^and Bfoaming^ (Araújo et al 2015;Jenkins et al 1993;Rossetti et al 2005;Wanner and Nielsen 2010). And it is reported that Microthrix parvicella (M. parvicella) is one of the dominant microorganism responsible for these problems (Kumari et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The sludge bulking is mainly associated with the excess growth of filamentous bacteria [2][3][4], and excess growth of filamentous bacteria results in the formation of a viscous thick stable foam, causing solid separation problems in WWTPs [5]. The Microthrix parvicella (M. parvicella) is one of the most famous microorganism reported to be responsible for these problems in activated sludge systems [6][7][8][9][10]. The excessive growth of M. parvicella in WWTPs can cause severe problems, like bulking and floating of sludge [5,11].…”
Section: Introductionmentioning
confidence: 99%